Homo Sapiens und Homo Faber: Epistemische und technische Rationalität in Antike und Gegenwart. Festschrift für Jürgen Mittelstraß - Carrier, Martin; Wolters, Gereon (De Gruyter, 2012)
Biographical note: Gereon Wolters is Professor of Philosophy at the Universität Konstanz, Germany. Martin Carrier is Professor of Philosophy at the Universität Bielefeld, Germany.
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Erkenntnistheorie; Wissenschaft; Methode